2007
DOI: 10.2109/jcersj2.115.546
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxations of Y-Doped ZrO2 Single Crystal

Abstract: Frequency dependences of dielectric constant e r ö for 9 mol! Y 2 O 3 doped ZrO 2 YSZ single crystal which is a typical oxide-ion conductor was successfully explained by the superimposition of both electrolyte-electrode interfacial and Debye-type polarizations. Three kinds of Debye-type polarizations were observed at fairly high temperatures. The two polarizations were ascribed to defect associates,, which were observed in the tan d spectra. The third polarization in the high frequency region was ascribed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…It is suggested that dispersion of σ ac occurs due to the dipole polarization and that impedance spectra indicates movement of dipole. In addition, we have been reported similar behavior in single crystal of 9mol% Y 2 O 3 stabilized ZrO 2 without grain boundary [10]. Therefore, the dispersion of σ ac in the oxide-ion conductors is not necessarily contribution by grain boundary resistivity.…”
Section: Transaction Of the Materials Research Society Of Japansupporting
confidence: 54%
See 1 more Smart Citation
“…It is suggested that dispersion of σ ac occurs due to the dipole polarization and that impedance spectra indicates movement of dipole. In addition, we have been reported similar behavior in single crystal of 9mol% Y 2 O 3 stabilized ZrO 2 without grain boundary [10]. Therefore, the dispersion of σ ac in the oxide-ion conductors is not necessarily contribution by grain boundary resistivity.…”
Section: Transaction Of the Materials Research Society Of Japansupporting
confidence: 54%
“…The detail explanations concerning the theoretical treatment of dielectric properties for oxide-ion conductors are given elsewhere [5][6][7][8][9][10]. Therefore, the apparent dielectric constant (ε r ′) can be given by the following equation (1), assuming the presence of various Debye-type dipoles with multiple relaxation times: (1) where ω, ε r0i , and τ i represent the angular frequency (=2πf), the dielectric constant at the low frequency limit due to the i-th Debye-type polarization and the i-th dipole relaxation time (=1/2πf i ), respectively.…”
Section: Transaction Of the Materials Research Society Of Japanmentioning
confidence: 99%
“…The dispersion in electrical properties was assigned to charge carrier relaxation and fitted to an approximately Gaussian distribution of relaxation times (17) . Single crystals of YSZ9 showed dispersions in permittivity, from which tan peaks were extracted and attributed to defect associates involving substitutional Y and oxygen vacancies (18) .…”
Section: Introductionmentioning
confidence: 99%
“…Our research group reported that the relationship between oxide ion conduction and dielectric relaxation from the viewpoints of dielectric constant, dielectric loss factor and loss tangent (tanδ) in the Sm, Nd, or Yb doped CeO 2 [4][5][6] and Y or Ca stabilized ZrO 2 [7,8] systems. According to those studies, the dielectric properties of oxide ion conductors can be explained by the superposition of Debye-type polarization due to the dopant-vacancy associates [Ln Ce ′-V O¨] ‧ (Ln: dopant cation) and charge current on electrolyte-electrode interface.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the dielectric relaxation measurement of 9 mol% Y 2 O 3 doped ZrO 2 single crystal was carried out to explain the grain boundary effect [7].…”
Section: Introductionmentioning
confidence: 99%